Parallel Computational Thinking: Applications must be programmed to process instructions in parallel to take full advantage of the new multicore processors. - Kirkpatrick, Keith (Communications of the ACM, 2017)
The article discusses the use of parallel computational thinking in programming applications to fully utilize multicore processors. Topics include the traditional use of sequential thinking in computer science education, the teaching of parallel computation as part of undergraduate computer science curricula, and the use of algorithmic models in relation to multicore device programming.